Measuring the Efficiency and Productivity of Cement Companies in the Tehran Stock Exchange Using Data Envelopment Analysis and Malmquist Productivity Index in Gray Environment - Farjam Kayedppour; Shadi Sayadmanesh; Yasamin Salmani; Zahra Sadeghi (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: In this study, the grey data envelopment analysis approach and the Malmquist productivity index were used to measure the efficiency and productivity of companies in the Tehran Stock Exchange cement industry. Methodology: First, we identify the appropriate financial ratios for measuring efficiency. Then, we calculate these ratios for each financial year as grey numbers (intervals). In the next step, these ratios are divided into two groups of input and output variables under research variables. Finally, the efficiency and productivity of the studied companies for the two fiscal years, 2018 and 2019, were determined using CCR and BCC models. Its components have been estimated. Findings: The results of this study provide a suitable framework for using uncertain information (grey) to replace definite information and thus allow more realistic results to be estimated about the performance of companies. Findings: The results of this study provide a suitable framework for using uncertain information (grey) to replace definite information and thus allow more realistic results to be estimated about the performance of companies. Originality/Value: This study uses the Malmquist-Grey Productivity Index to provide a framework for comparing productivity changes over time. This index measures the ratio of the measured efficiencies of a production unit in two different periods.